The Role of Agriculture and Agrarian Sectors in the Azerbaijan Economy: Main Trends and Dynamics since 1991 - Ibrahim Niftiyev (SSRN, 2020)
Agriculture and agrarian sectors have been gone through the serious transformation process since the collapse of the Soviet Union in Azerbaijan. An ever-growing body of academic literature body investigated the resource curse and Dutch disease theories to conceptualize non-oil sectors in Azerbaijan starting from the late 1990s; however, the unanimous conclusion about the status of agriculture, agrarian sectors or manufacturing is still highly anticipated. Modern statistical techniques and accumulated data on the crucial economic indicators allow us to conceptualize the main trends and dynamics of agriculture and agrarian sectors in the context of resource-richness in Azerbaijan. This paper aims to descriptively investigate the collected data related to agriculture and agrarian sectors. Special emphasis has been put on the theoretical relevance of Dutch disease and resource curse to operationalize the research interest and research question. The findings of the correlation analysis show that there is a positive, significant, and strong association between the real effective exchange rate of Azerbaijan and international oil prices. The other findings demonstrate that mainly agriculture-related variables decreased their role in the Azerbaijan economy since 1991 but only value-added per worker gradually rose, also correlating negatively with value-added in agriculture and investments in agriculture.
Keywords: 330; Azerbaijan economy; agriculture; agrarian sectors; polynomial regression trendline; correlation analysis